Pengaruh Penggunaan Media Permainan Ular Tangga Kimia Berbasis Android Materi Asam Basa terhadap Hasil Belajar Peserta Didik Fase F SMA/MA - Salsabila Hasna Putri; Iswendi Iswendi (Lembaga Yasin AlSys, 2025)
This study was motivated by the availability of an Android-based Snakes and Ladders Chemistry educational game on the topic of acids and bases, which has been proven valid, practical, and effective yet its influence on students' cognitive learning outcomes remains unexplored. The aim of this research is to analyze the effect of using this media on the cognitive learning outcomes of Phase F senior high school students. The research employed a quasi-experimental design using a Post-test Only Control Group Design. The population consisted of all Grade XI Phase F students at SMA Negeri 2 Lubuk Basung, with random sampling used to select XI Chemistry 1 as the control group and XI Chemistry 2 as the experimental group. The instrument used was a cognitive learning outcome test. Data analysis included normality testing, homogeneity testing, and hypothesis testing using a t-test. The results showed that the average post-test score of the experimental class was 75.7, while the control class scored 62.5. The t-test result indicated that tcount (2.89) > ttable (1.70) at a significance level of α = 0.05, meaning that the use of the media had a significant effect on learning outcomes. The study concludes that the Android-based Snakes and Ladders Chemistry game positively influences students’ cognitive learning outcomes in the topic of acids and bases.